PENGARUH KELAS PENCEGAHAN STUNTING TERHADAP PENGETAHUAN IBU TENTANG PEMENUHAN GIZI BAYI USIA 6-12 BULAN DI WILAYAH KERJA PUSKESMAS SIDOMULYO - Aldinda, Tharra Widadari; Pesa, Yadriati Maya; Zalni, Rummy Islami; Masfufa, Tentya Indah; Reti, Herlita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Nutrition is a process of using food that is consumed normally through the processes of digestion, absorption, transportation, storage, metabolism and excretion of unused substances to maintain life, growth and normal function of organs and produce energy. Improper feeding will disrupt the nutritional status and health of the baby. At the age of 0-6 months, babies should only be given exclusive breast milk (ASI). However, starting from the age of 6-12 months, babies no longer get sufficient nutritional intake from breast milk alone, so they must be given complementary foods (MPASI) gradually from liquid food to solid food. The aim of this research is to analyze the influence of stunting prevention classes on mothers' knowledge regarding nutritional needs for babies aged 6-12 months in the Sidomulyo Community Health Center working area. This research uses a quantitative approach, the method used in this research is quasi experiment. The sample in this study was 89 respondents. The method for determining the sample is cluster sampling. The data collection tool is a questionnaire and data analysis uses Chi-Square with ???? = 0.05. The results of this study show that there is an influence of stunting prevention classes on mothers' knowledge about fulfilling nutritional requirements for babies aged 6-12 months (Pvalue 0.000). stunting incidence rate.Keywords: Class, Stunting, Knowledge, Nutrition